SEPARATION OF PENICILLING FROM FERMENTATION BROTH BY EMULSION LIQUID MEMBRANETECHNIQUE Pemisahan Penisilin GHasil Fermentasi dengan Teknik Membran Cair Emulsi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT The separation of penicillin G from fermentation broth can be done by emulsion liquid membrane technique. The aim of this research is to establish the optimal conditions for the extraction and separation of penicillin G using emulsion liquid membrane technique. The optimal conditions were found to be at ratio of internal phase volume to membranephase volume of 1:1